SOS1 is the second most common Noonan gene but plays no major role in cardio-facio-cutaneous syndrome. Issue 10 (23rd June 2007) - Zenker, Martin; Horn, Denise; Wieczorek, Dagmar; Allanson, Judith; Pauli, Silke; van der Burgt, Ineke; Doerr, Helmuth-Guenther; Gaspar, Harald; Hofbeck, Michael; Gillessen-Kaesbach, Gabriele; Koch, Andreas; Meinecke, Peter; et al.
Abstract : Background: Heterozygous gain-of-function mutations in various genes encoding proteins of the Ras-MAPK signalling cascade have been identified as the genetic basis of Noonan syndrome (NS) and cardio-facio-cutaneous syndrome (CFCS). Mutations of SOS1, the gene encoding a guanine nucleotide exchange factor for Ras, have been the most recent discoveries in patients with NS, but this gene has not been studied in patients with CFCS. Methods and results: We investigated SOS1 in a large cohort of patients with disorders of the NS–CFCS spectrum, who had previously tested negative for mutations in PTPN11, KRAS, BRAF, MEK1 and MEK2 . Missense mutations of SOS1 were discovered in 28% of patients with NS. In contrast, none of the patients classified as having CFCS was found to carry a pathogenic sequence change in this gene. Conclusion: We have confirmed SOS1 as the second major gene for NS. Patients carrying mutations in this gene have a distinctive phenotype with frequent ectodermal anomalies such as keratosis pilaris and curly hair. However, the clinical picture associated with SOS1 mutations is different from that of CFCS. These findings corroborate that, despite being caused by gain-of-function mutations in molecules belonging to the same pathway, NS and CFCS scarcely overlap genotypically.